2019
DOI: 10.3389/fpsyg.2019.02839
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Dynamics of Infant-Adult Synchrony Through Mocap

Abstract: The temporal dynamics of parent-infant synchrony have been well documented. In recent years, the introduction of more accurate technologies for tracking movements has allowed the distinction of different morphological patterns of dyadic coordination. However, the potential of these technologies to explore infant-adult synchrony has not yet been explored. In the present study, we examined the temporal, spatial, and morphological synchrony patterns of infant-unknown adult pairs participating in a storytime sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…This is especially true in the case of behavioral synchrony, which unfolds across multiple time scales. By analyzing continuous spatial and temporal data, we join others (e.g., Chow et al, 2018; Cuadros et al, 2019; López Pérez et al, 2017; Xu et al, 2020; Yu & Smith, 2013) in championing the feasibility and advantages of using real‐time techniques to measure dyadic behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true in the case of behavioral synchrony, which unfolds across multiple time scales. By analyzing continuous spatial and temporal data, we join others (e.g., Chow et al, 2018; Cuadros et al, 2019; López Pérez et al, 2017; Xu et al, 2020; Yu & Smith, 2013) in championing the feasibility and advantages of using real‐time techniques to measure dyadic behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Although behavioral synchrony underlies many forms of social interaction, its development has been studied primarily during stationary, face‐to‐face interactions between infants and caregivers or other adults (Cohn & Tronick, 1987; Cuadros, Hurtado, & Cornejo, 2019; Kaye & Fogel, 1980; López Pérez et al, 2017; Stern, 1971, 1974). While held in their mother’s arms or seated across from one another, pre‐mobile infants and their caregivers spontaneously engage in a sequence of contingent facial expressions and vocalizations that researchers have referred to as a social “dance” (Bernieri et al, 1988; Feldman, 2007; Harrist & Waugh, 2002; Jaffe, Beebe, Feldstein, Crown, & Jasnow, 2001; Provenzi, Scotto di Minico, Giusti, Guida, & Müller, 2018; Stern, 1997; Yale, Messinger, Cobo‐Lewis, & Delgado, 2003).…”
Section: Current Studymentioning
confidence: 99%
“…This represents a substantial contribution to the literature considering that there have been no studies to date which have examined tactile synchrony in a manner that captures dynamic changes in both maternal and infant touch. Previous studies exploring the concept of tactile synchrony have either failed to examine infant touch altogether (e.g., Feldman et al, 2010), or have neglected to examine infant touch during mother-infant interactions (Cuadros et al, 2019;Della Longa et al, 2020), consequently overlooking the bidirectionality of touch and the context (e.g., setting of interaction, positioning of dyad) most likely to foster synchrony. Findings within the current investigation revealed that in the lap context, increases in mothers' use of stroke/caress (soft and gentle movements displayed in a lateral or circular manner) were associated with increases in infants' use of this same type of touch over time.…”
Section: 2mentioning
confidence: 99%
“…The differences found at zero-lag on spontaneous and nonspontaneous synchrony accurately measured seem to add evidence to the hypothesis that coordination in natural interactions is discontinuous temporally. Studies on interpersonal coordination in face-to-face social encounters show that synchronous co-activity emerge swiftly and for brief periods [3,46,54,66,132].…”
Section: Time and Morphology Of Synchronymentioning
confidence: 99%
“…Observational research has approached synchrony in terms of observable body patterns of parent-infant matching in mutual attention periods [ 56 , 64 ]. In these works, synchrony is quantified from detailed coding and scoring techniques of spontaneous dyadic events, such as microanalysis or behavioral coding [ 64 66 ]. By estimating frequencies, durations, and concurrences, observational studies evidenced that baby-mother matching exhibits coherent body patterns in timing and rhythm even as early as the first day of life [ 46 , 54 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%